Effectiveness of first-line anticancer treatment may predict treatment response in further lines in stage III/IV patients with non-small cell lung cancer - Bratova, Monika; Skrickova, Jana; Matusikova, Magda; Hrabcova, Karolina; Havel, Libor; Koubkova, Leona; Hrnciarik, Michal; Krejci, Jana; Fischer, Ondrej; Svaton, Martin; Brat, Kristian (Journal of cancer research and clinical oncology, 2023)
PURPOSE: The aim of our study was to evaluate if therapeutic success in the first-line of anticancer treatments in patients with NSCLC may predict treatment success in the following lines. METHODS: We analyzed the data of patients with NSCLC stage III/IV from the TULUNG registry separately for chemotherapy, TKIs, ALK inhibitors, and immunotherapy in the first line during the years 2011-2019. "Succesful treatment " was defined as PFS ≥ 6 months, a "good responder " was a patient with ˃50% of "successful treatment " lines. Treatment responses were analyzed separately for each drug group. Descriptive statistics, Fisher exact test, Pearson Chi-Squared test, log-rank test, and univariate/multivariate logistic regression models were used. RESULTS: The first-line TKI therapy was successful in 66.2%, while good responders accounted for 50.7% of the cohort and their rates were similar for all types of TKIs. First-line platinum-based chemotherapy was successful in 43.1% and 48.6% for combinations with pemetrexed and bevacizumab, respectively. Good responders accounted for 29.5% and 25.9%, respectively. In the group of ALK inhibitors, we observed treatment success in 52.3% of cases, while alectinib showed the highest effectiveness (up to 70%). Good responders constituted 50% of the group. In the first-line immunotherapy group, survival benefit was observed in 52.3%, and good responders constituted 52.3% of the cohort. CONCLUSION: We concluded that the treatment success in first-line therapies in patients with NSCLC may predict survival benefits in the subsequent lines, particularly in EGFR- or ALK-positive disease and immunotherapy-treated patients.
Keywords: pemetrexed; Humans; nemalobuněčný karcinom plic; Effectiveness; Lung Neoplasms; Pemetrexed; Non-small cell lung cancer; Anticancer treatment; erbB receptory; nádory plic; Protein Kinase Inhibitors; Overall survival; inhibitory proteinkinas; ErbB Receptors; Carcinoma, Non-Small-Cell Lung; lidé; Bevacizumab; Progression-free survival; bevacizumab